OVERVIEW OF EMOTIONAL DYSREGULATION OF STUDENTS VICTIMS OF BULLYING IN JUNIOR HIGH SCHOOL AND ITS IMPLICATIONS FOR COUNSELING INTERVENTIONS - Syekha Aulia Mutia Zahra; Eka Wahyuni; Susi Fitri (Jurnal Konseling Pendidikan Islam, 2026)
Emotion dysregulation is a problem that occurs in any or all emotion regulation abilities. The occurrence of emotion dysregulation can lead to various mental health problems. This study aims to describe the level of emotion dysregulation of students who are victims of bullying in junior high school and its implications for counseling interventions. The research used a quantitative approach with a survey method. The sampling technique used convenience sampling technique with a total research sample of 108 junior high school students. Data collection was carried out through the Difficulties in Emotion Regulation Scale Short Form (DERS-SF) instrument, while data analysis techniques used descriptive statistics. The category is high in emotion dysregulation if X ≥ 54, while the category is low in emotion dysregulation if X < 54. The results of the analysis on students who are victims of bullying show that 41 students (37.96%) have a high level of emotion dysregulation and 67 students (62.04%) have a low level of emotion dysregulation. Based on the results of this analysis, it is found that the majority of the level of emotional dysregulation of students who are victims of bullying at one private junior high school in East Jakarta is in the low category. However, there are still many students who are victims of bullying in junior high schools who have high levels of emotional dysregulation, so efforts to reduce the emotional dysregulation of students who are victims of bullying in junior high schools are very important for guidance and counseling teachers to do. One of the effective counseling interventions used is Acceptance and Commitment Therapy (ACT).